Analisis Faktor Dalam Pemanfaatan Layanan Voluntery Counseling And Testing (VCT) Pada Pelanggan Wanita Pekerja Seks (WPS) Di Lokalisasi Lorong Indah Kabupaten Pati - Wicaksono, Aditya; Isworo, Atyanti; Alivian, Galih Noor (Journal of Bionursing, 2019)
Background: The key population groups, female sex worker (FSW) customers, are still low in utilizing voluntary counseling and testing (VCT) services. This study aims to determine the factors that influence FSW customer behavior in utilizing VCT services.Methodology: This study used a cross sectional design. The samples were 95 FSW customers with accidental sampling technique. The instrument of this study used a questionnaire. The analytical methods were univariate analysis and bivariate analysis using Chi Square.Research Results: The results of this study indicate that the majority of respondents aged 36-45 years have education with a senior high school / university level and most work as entrepreneurs. There was a significant relationship between self-fear factor and the use of VCT with a p-value of 0.016 and other people's support factors with the use of VCT services with p-value 0.001. However, there was no significant relationship between the knowledge factor and the use of VCT services with p-value 0.052.Conclusion: There are a significant relationship between the factors of self-fear and the support of others with the use of VCT services.